2023
DOI: 10.1002/ejsp.2951
|View full text |Cite
|
Sign up to set email alerts
|

Lay theories about collective power in the context of racial oppression

Abstract: Social psychological research has generally assumed that oppressed groups are powerless because they often have less control over resources and outcomes and power is usually defined as dominance or influence and control. We juxtapose this theoretical assumption with lay beliefs about the ingroup's collective power expressed in semi‐structured interviews among Black Americans (N = 28). Thematic analysis revealed that participants’ beliefs about ingroup power varied: whereas some participants perceived that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Participants promptly articulated the fatal couplings through various accounts of coloniality, assimilation, criminalization, and violence by the Turkish state, and as demonstrated in daily intergroup relations. Such strong accounts also correspond to the ways in which racially oppressed groups counternarrate the asymmetrical power dynamics embedded in all walks of life, which can be better understood at different levels of society in various types of relationships (Salter & Haugen, 2017;Twali et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Participants promptly articulated the fatal couplings through various accounts of coloniality, assimilation, criminalization, and violence by the Turkish state, and as demonstrated in daily intergroup relations. Such strong accounts also correspond to the ways in which racially oppressed groups counternarrate the asymmetrical power dynamics embedded in all walks of life, which can be better understood at different levels of society in various types of relationships (Salter & Haugen, 2017;Twali et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…With regard to social psychological conceptualizations, such as power over and power from below (i.e., power to, power from, power with, power within, and power through), participants' understandings of Kurdish power over was a generic understanding of power as control over resources, a longing for a hegemonic central force, including the state and the interest disputes among different political groups (Simon & Oakes, 2006). Twali et al's (2023) recent research also indicated a similar understanding among Black Americans. Furthermore, antiessentialism was manifested in a dilemmatic way; while a critical consciousness about systematic racialization and essentialist lack of recognition by Turks is well-articulated and acts as a catalyst to reclaim Kurdishness, for some participants, it is not transferred to a nonessentialist understanding of Kurdishness, partially reproducing a hegemonic sense of nationalism (Amer & Obradovic, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations